Photoluminescence studies of In0.5Ga0.5As/GaAs quantum dots - Wahab, Yussof (2006)

(untitled)
In this paper, we present an experiment study of the photoluminescence properties of self-assembled In0.5Ga0.5As/GaAs quantum dots (QDs). High quality In0.5Ga0.5As QDs were grown by using Metalorganic Chemical Vapor Deposition (MOCVD). The low temperature photoluminescence (PL) spectrum of the In0.5Ga0.5As quantum dots surrounded by GaAs exhibit an emission peak at 1.137 to 1.182eV and a narrow linewidth (FWHM). The PL peak energy and intensity are varied with the excitation powers. Room temperature PL shows slightly lower peak energy with a broader spectrum linewidth. The distribution of the peak energy, peak intensity, and FWHM for the whole sample was obtained by using the PL mapping method.